Numerical Simulation Of Modified Rubberized Concrete Block Under Impact Loads - Teo, Yu Pei; Mokhatar, Shahrul Niza; Abdul Mutalib, Nur Anis Najwa (Recent Trends in Civil Engineering and Built Environment, 2022)
Rubberized Concrete was innovated by many researchers to enhance energy absorption under impact load and by reusing scrap tires. Thus, this research was aims to develop the numerical procedure using the Finite Element Method (FEM) to simulate modified rubberized concrete under impact loads and predict its energy absorption under different impact loads. Three existing constitutive models: Concrete Damage Plasticity (CDP), Drucker-Prager (DP), and Modified Drucker-Prager Cap (MDPC) available in ABAQUS software were used to replicate the rubberized concrete with 10% of Rice Hush Ash (RHA) as cement substitution and different percentages (0%, 5%, 10%, 15%, and 20%) of crumb rubber as sand replacement. All three models produced successful FEM results with reasonable modelling assumption, and the CDP model was more effective in simulating rubberized concrete under impact to predict energy absorption than DP and MDPC models. Further, it was concluded that crumb rubber could enhance the performance energy absorption of concrete. Generally, the energy absorption of the concrete increased as the crumb rubber increase. However, the strength decreased as the crumb rubber increased, but 10% of RHA in concrete mix can maintain the concrete strength. Overall, this study reveals that FEM incorporated with CDP model are able to predict the impact response of modified crumber rubber as an application of concrete road barrier.